Acercamiento de la situación epidemiológica de Coxiella burnetii en Suramérica (2020)
Coxiella burnetii is an intracellular, gram negative, spore-producing bacterium. It is characterized by being the etiologic agent of Q fever, a zoonosis that reports clinical affectations in humans and animals. Although it is not a high mortality disease, it is a debilitating pathology that could be avoided with early diagnosis and simple antibiotic treatment. Due to the limited information about the C. burnetii in South America, a systematic review of the epidemiology of this agent between the years 2000-2020 was done in order to consolidate the reported information. This review was accompanied by an evaluation of the presence of IgG Phase II antibodies in a population of Montelíbano, Córdoba. Epidemiological data evidenced the circulation of this agent in humans, animals and even food, with variable seropositivity values in terms of region regarding humans and animals. Infection by this bacterium can generate different clinical manifestations. In humans, those associated with the acute phase present the most registered cases while most animals suffered reproductivity affections. The risk factors are not clear yet, but in humans occupation and contact with animals are among the most common ones; whereas in animals the type of breed and sex are mainly suggested. In Colombia, the data suggest a seropositivity of 3.26% for the population analyzed in Córdoba. Consequently, it is evident that C.burnetii presents a real and underestimated threat to South America; reason why C.burnetii should be included in the differential diagnosis of diseases in the region.